EMPLOYMENT OF THE POPULATION AND PROBLEMS OF UNEMPLOYMENT IN THE STAVROPOL TERRITORY - A. Bashtova; E. Kalashnikova; E. Nemtsova; Y. Chernikova (Вестник Северо-Кавказского федерального университета, 2022)
One of the most importantfactors that affect the well-being of a society is its employment. This factor is closely related to the emergence of a socio-economic situation, such as unemployment, which, in turn, has affected millions ofpeople in the past year. The article presents the analysis and results of employment of the unemployed population in the Stavropol Territory. At the same time, the number of officially registered unemployed citizens in the region and the coefficient of tension in the labor market are analyzed, and the main causes of unemployment in the region are identified. The number of the labor force in the period for 2018-2019 was studied, and the number of unemployed in the region was also analyzed. The results of the state programs, the assessment of the provided consulting assistance for the analyzed period and the results of the job fairs are presented. It is concluded that the above results have reduced the number of officially unemployed citizens, which indicates a favorable trend. The efectiveness of the state service in the ight against unemployment is studied. The Employment Service helps to improve the skills of disabled people for their further employment. To date, it is impossible to completely prevent unemployment, but it is necessary to minimize it.